SISTEM BAGI HASIL PENGGARAPAN SAWAH DI DESA PARIA KECAMATAN DUAMPANUA KABUPATEN PINRANG - liya Saputri (Prodi Manajemen Universitas Syekh Yusuf Al Makassari Gowa, 2025)
This study aims to determine the Profit Sharing System in Paria Village, Duampanua District, Pinrang Regency. The type of research used is a qualitative research method. The data obtained are the results of interviews and observations from the Owner Farmers and Cultivators. In this study, the data sources used in data collection include primary data and secondary data. The data analysis technique used in this study uses descriptive, namely a way of thinking that departs from specific facts and concrete events to be generalized. The results showed that the profit-sharing system carried out by the community in Paria village orally on the basis of mutual trust and as a family. The profit-sharing system is divided into 3, where the sharecropper gets 2 shares and the owner farmer gets 1 share. with an agreement that has been agreed that all costs for working on the fields are borne by the tenant farmers. Constraints faced are crop failure caused by pests, insufficient water or drought and lack of capital. The way to overcome obstacles in the event of crop failure is to communicate directly with the land owner regarding the obstacles encountered